To See and To Be Seen: On Vision and Perception in Lucretius and Cicero - Reinhardt, T (Oxford University Press, 2015)
This chapter offers a detailed analysis of perception verbs—with special focus on the forms uidere and uideri—in Lucretius’s De rerum natura and Cicero’s Academica. The chapter’s approach to those forms is first defined by appeal to the model of preference rule systems used in cognitive linguistics. Through exploitation of the different qualities of seeing that uidere/-eri accommodate, the chapter’s Lucretius privileges how things look to a perceiving subject over how they actually are; the chapter’s Cicero similarly exploits the flexibility of uidere/-eri to demarcate Stoic and Academic modes of perception in the Academica. The chapter’s further agenda is to relate these exploitations of different nuances of uidere/-eri to Lucretius’s and Cicero’s larger interaction with their Greek source-texts: the case of uidere/-eri promotes reflection on the preexisting resources and capacities of the Latin language in relation to its Greek models, and ultimately on Latin’s empowerment as a medium for writing philosophy.